HUBUNGAN ANTARA LAMA DIABETES DENGAN EFIKASI DIRI PASIEN DIABETES MELITUS TIPE 2 - Clara (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2024)
Diabetes mellitus (DM) is a chronic disease with increasing incidence and prevalence worldwide. The risk of complications that can occur in patients with type 2 DM includes acute complications and chronic complications. To prevent the onset of the above complications, it is necessary to control diabetes through the application of correct and regular self-management behavior every day. One factor that is thought to be related or a predictor of self-management behavior is self-efficacy. The research design used was cross sectional, with a sample size of 112 respondents. The measuring instrument used The Diabetes Management Self Efficacy Scale (DMSES). The results showed a significant relationship between the length of time with diabetes and self-efficacy (p value <0.05). This significant relationship can be caused by people with diabetes who have been diagnosed for a long time may already understand the procedures for diabetes self-care so that they feel more confident to carry out self-management. Therefore, it is important for nurses to help improve the self-efficacy of people with type 2 diabetes through providing education about type 2 diabetes management, as well as providing support and motivation.